The factors of consumer confidence recovery after scandals in food supply chain safety. Issue 5 (26th November 2018) - Wang, Shuhui; Alexander, Paul
Abstract : Purpose: Viewing consumer confidence as a set of static factors has informed previous research and underpinned strategies used in recovering from food safety quality failures, but this approach has not delivered reliable and quick recovery from large-scale food safety scandals. The purpose of this paper is to examine extant models and the factors they are composed of, and suggest an extended model that has a better potential for consumer confidence. The paper focuses on food products where supply chains are visible, and use these features to group the findings. Design/methodology/approach: In this study principal components and logit analyses are used to assess the role of 30 variables operating in a consumer confidence model constructed from several existing in the literature. This combined model considers emotional, cognitive, trust and sociodemographic factors. In total, 14 independent factors are identified. The authors examine the factors, and from these, the decision-making mechanisms before and after the Sanlu Infant Milk Formula (IMF) scandal of 2008. Findings: The authors find that the factors considered by consumers are different for different IMF supply chains, and different again before and after the scandal. The authors develop the argument for an extension to the existing models, incorporating a dynamic consumer confidence system. Research limitations/implications: The paper uses a single survey after the focus event to establish "before" and "after" decision-making factors. Since the IMF scandal is recent and of very high profile, this is likely valid even if it carries memory bias effects. The study is directly applicable to food safety scandals in a Chinese context. Deductive reasoning extends our assertions to a wider context. They are logically validated but have not been formally tested. Practical implications: Using this system as a framework a checklist for recovery from a similar food safety scandal is suggested. The authors also suggest more general use for use where supply chains features are visible to consumers. Originality/value: Models for food safety consumer confidence recovery have previously focused on identifying models and the static factors they consist of. These do represent a reflection of how this phenomenon operates, but using the principals of this model nevertheless does not result in good recovery from extreme food safety failures. This paper contributes by extending these models to one that can be applied for better recovery.